VISI, MISI, TUJUAN DAN FUNGSI PENDIDIKAN ISLAM - Daulay, Haidar Putra; Dahlan, Zaini; Wibowo, Gumilang; Lubis, Jukni Ilman (Jurnal Ilmiah Al-Hadi, 2020)
Education is a process that is carried out consciously or deliberately in order to increase knowledge, insight and experience to determine life goals so that they can have a broad view towards a better future and with education itself can create quality people. As Western theory, educators in Islam are people who are responsible for the development of their students by trying to develop all the potential of students, both affective (feeling), cognitive (creativity), and psychomotor (intention) potential. Education is a cultural process to enhance human dignity that lasts a lifetime. Education is always developing, and always faced with changing times. Such is the cycle of development of change in education, otherwise education will be left behind by the changing times that are so fast. For that change in education must be relevant to changing times and the needs of society in that era, so it is important to design as early as possible which can be outlined in the Vision, Mission, Objectives and Functions of Islamic Education